Consensus and conformity - Allen, Vernon L.; Levine, John M.; Wisconsin Univ., Madison. Research and Development Center for Cognitive Learning ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
In this study, professor allen employs two methods of breaking group consensus, and he measures the effects on the responses of college subjects to both objective and subjective stimuli. The results suggest the need for modification of existing theories of conformity behavior. In addition, these results emphasize the differences in conformity of males and females. Group consensus was broken either by a partner agreeing exactly with the subject (s) (social support) or by a dissenter giving a response even more incorrect than the group's (extreme dissent). Using the crutchfield apparatus, 157 male and female ss responded to visual, information, and opinion items. Results disclosed that extreme dissent, in comparison with an unanimous group, significantly decreased conformity on visual and information but not on opinion items. Social support significantly reduced conformity on all three types of items for males, and on visual and information items for females. The results cast doubt on asch's contention that breaking group consensus, per se, is responsible for the effectiveness of social support in reducing conformity. (author)
Contract Number: OEC-5-10-154.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior; Behavior Theories; Conformity; Group Behavior; Social Attitudes; Social Influences